PEMANFAATAN JAMUR ENDOFIT DARI DAUN MURBEI (Morus alba L.) SEBAGAI ANTIBIOTIK - Sukriani Kursia; Alimuddin Ali; Fitriyanti Jumaetri Sami; Rabiatul Adhawiyah (As-Syifaa Jurnal Farmasi, 2017)
Endophytic fungi are fungi colonize internally plant tissue, without giving detrimental effect to the host plant. They act as symbiont, mediated plant resistance against biotic stress i.e. pests and diasease and abiotic stress such as drought and extreme of temperature. Endophytic fungi are one of the most creative groups of secondary metabolite producers that play important biological roles for human life. Fungi are among the most important groups of eukaryotic organisms that are well known for producing many novel metabolites which are directly used as drugs or function as lead structure for modification.Mulberry (Morus alba L.) is one of the genus species known to have secondary metabolite compound that can be used as an antioxidant, antibacterial, antiviral, antidiabetic, antihypertensive, hypolipidemic, fever, flu, cough, antiemetic and gastrointestinal disorders. This research aimed to determine antibacterial activity of Mulberry Fungi from the leaves against the bacteria Escherichia coli and Staphylococcus aureus. Isolation of endophytic fungal carried by the direct isolation techniques. Isolates which produced as much as 3 isolates the MUR1, MUR2 and MUR3. Further isolates fermented using PDY medium and extracted using ethyl acetate. The ethyl acetate extract qualitative test the activity against bacteria Escherechia coli and Staphylococcus aureus. The result of the antibacteria activity, ethyl acetat extract from fermentation medium PDY of Mulbery (Morus alba L.) inhibited growth of Escherechia coli and Staphylococcus aureus at > 12 mm Keywords: Endophytic fungi, Mulberry (Morus alba L.), Antibiotic.